The management of post-stroke pain - Nina Devi Indrawati; Laily Irfana; Yelvi Levani (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2024)
Stroke is a metabolic illness that causes significant impairment in the working-age population. Disability develops due to the consequences of neurological deficiencies and the failure of the medical rehabilitation process. Post-stroke pain is one of the causes of this failure. In a post-stroke patient, pain is an unpleasant physical and emotional experience. In contrast, range of motion barriers might cause the medical rehabilitation procedure to fail. This paper aims to review the various methods of post-stroke pain management that can be used as an alternative therapy that helps post-stroke patients' rehabilitation. The PubMed database was used to search for different kinds of literature. The study includes clinical studies, pilot studies, and randomized control trials published between January 2015 and June 2023. The authors omit several publications to ensure that the final selection of papers includes only the most relevant and reputable sources of information on post-stroke pain, post-stroke pain management, and pain as a measure of outcome. There are 28 publications to be reviewed. The most prevalent cause of post-stroke pain was hemiplegic shoulder pain in numerous studies that have an impact on the post-stroke recovery process. In conclusion, the options for post-stroke therapy range from conservative rehabilitation to interventional therapy. Several innovative experimental rehabilitation treatment approaches have been studied. However, the findings do not outperform conventional rehabilitation treatment.